The role of NATO in shaping the global security system. Reflections on the 70th anniversary of the founding of the organization (Academic Journal of Internal Affairs, 2020)
NATO has survived until its 70th anniversary, essentially in the same condition as practically every year of its existence. According to commentators and external experts, the Alliance seems to be in a constant crisis, and every new version of the crisis is seen as final and deadly. By contrast, for those who are active internally, NATO seems stronger than ever before - it is engaging in more places than ever before, presenting new initiatives at an unprecedented pace and in ever-longer summit declarations. The problem situation presented in this way allows us to formulate the main research problem: What role does NATO play in shaping the global security system? The research problem formulated in this way consists of detailed problems formulated in the form of questions: 1) What are the current challenges for NATO? 2) What are the current threats to NATO? 3 What is Donald Trump's policy towards NATO? The presentation aims to present an analysis of the role of NATO in ensuring collective security in the context of the 70th anniversary of the founding of the organization. The research process uses methodological methods of scientific cognition, mainly analysis and criticism of literature.
Keywords: NATO; security; Russian Federation; Donald Trump